Determining the sequence of extracting Pinus radiata bark to maximize the total yield of extractives–towards the development of a bark-based biorefinery - Sumanth Ranganathan; Sylke H. Campion; Reid A. Dale; Queenie L. Tanjay; Rachel H. Murray; Anna de Lena; Michael Robertson; Armin Thumm; Mark West (Bioresources and Bioprocessing)
Abstract Pinus radiata is the dominant tree species in exotic plantation forestry of New Zealand producing timber for construction and pulp and paper. Additionally, the processing yields large amounts of bark as a byproduct that is either left at the harvest site or used for landscaping. P. radiata bark is rich in biochemical extractives containing polyphenols and waxes on sequential extraction with hydrophilic and lipophilic solvents, respectively. Previous studies have exclusively focussed on the effect of parameters such as solvent type, bark to solvent ratio, and extraction time on the yield of extractives. However, two parameters were always maintained constant: solvent order (lipophilic to hydrophobic) and particle size. This work investigated the the combined impact of these two parameters on total yield and product quality by using two solvents- water and hexane. Total extractives were highest when water was used first (11.74% and 9.45%) compared to hexane (10.53% and 6.53%). The individual yields of hexane extractives were in the range of 2.25–2.9% while those of water were 4.30–9.24%. Chemical analyses of the extracts and residues showed no qualitative differences, indicating the order in which bark is extracted does not alter the extract composition. Moreover, the results have successfully established that extracting bark with water first followed by hexane will increase the total yield of extractives and increasing particle size decreases the total yield of the sequential extraction. Graphical Abstract